Impacts of oil and gas development on duck brood abundance. Issue 7 (28th August 2019) - Kemink, Kaylan M.; Gue, C. Tanner; Loesch, Charles R.; Cressey, Ryann L.; Sieges, Mason L.; Szymanski, Michael L.
ABSTRACT: The extraction of oil and natural gas from reserves in the Bakken Formation has increased from 2004 to 2017 in North Dakota and northeast Montana, USA. High development areas overlap substantially with wetlands and grasslands identified as high priority for waterfowl conservation in the Prairie Pothole Region. To test for anthropogenic disturbance on waterfowl brood abundance, we conducted repeat‐visit waterfowl brood surveys during 2014–2017. We tested hypotheses about disturbance and brood abundance using hierarchical zero‐inflated Poisson models and a spatially and temporally explicit disturbance index within 3 radii (0.32 km, 0.64 km, 1.51 km). Model selection supported detection and abundance parameters that were consistent with previous research and suggested that brood abundance was higher in landscapes with high densities of small, shallow wetlands. Our analysis also demonstrated a negative relationship between abundance and the disturbance index for the smallest spatial radius (0.32 km); however, the effect size was small and predictions suggested that <1% of the broods in the sample population were affected. Considering this relatively weak negative relationship and the continued role of wetlands as the primary factor influencing brood abundance, we recommended that managers continue to focus conservation efforts in landscapes with high densities of small, unprotected wetlands, even in the presence of oil and gas development. © 2019 The Authors. Journal of Wildlife Management Published by Wiley Periodicals, Inc. on behalf of The Wildlife Society. Abstract : Our analysis demonstrated a negative relationship between oil and gas disturbance and duck brood abundance. Because the effect size of this relationship was relatively small, we suggested that conservation efforts should continue to focus in landscapes of high value to waterfowl even in the presence of oil and gas development.